2022
DOI: 10.3390/children9060879
|View full text |Cite
|
Sign up to set email alerts
|

Nirvana: A Qualitative Study of Posttraumatic Growth in Adolescents and Young Adults with Inflammatory Bowel Disease

Abstract: (1) Background: Psychosomatic discomfort is prevalent among adolescents and young adults (AYAs) with inflammatory bowel disease (IBD). Post-traumatic growth (PTG) has been a protective factor in earlier research. However, little is known regarding PTG among AYAs with IBD. This study investigates the generation of PTG in adolescents and young adults with inflammatory bowel disease (IBD) and finds positive coping skills employed in clinical nursing practice. (2) Methods: In 2021, 32 individuals were interviewed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 56 publications
1
7
0
Order By: Relevance
“…Participants seemed to have drawn on their own resources to adjust to their illness, which led to positive evolutions. In fact, similarly to previous findings [30], their adjustment process seemed to allow a post-traumatic growth [36,37]. The diagnosis of CD appeared to create a real rupture in their daily lives through the limitations and changes it imposed.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Participants seemed to have drawn on their own resources to adjust to their illness, which led to positive evolutions. In fact, similarly to previous findings [30], their adjustment process seemed to allow a post-traumatic growth [36,37]. The diagnosis of CD appeared to create a real rupture in their daily lives through the limitations and changes it imposed.…”
Section: Discussionsupporting
confidence: 79%
“…However, a specificity of our results on young adults was the identity challenges and concerns about physical transformations that our analyses revealed and that were not so prevalent in the adult population. Moreover, if all previous studies reported the negative repercussions and challenges that patients can face and, even though two studies revealed the presence of positive outcomes in IBD [17,30], the interviews that we conducted highlighted the evolutions in the adjustment to CD and more specifically the process by which French young adults evolved positively despite the challenges and how they integrated their illness with their identity.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Together, the above research indicates that some patients with Crohn’s disease experience posttraumatic growth. However, few published studies [ 22 , 29 , 30 ] have focused on the process of posttraumatic growth in these patients. The insight from breast cancer [ 25 ] may not be applicable to the Crohn’s disease population given the difference in gender and age.…”
Section: Introductionmentioning
confidence: 99%
“…These ndings provide knowledge on the process of posttraumatic growth in patients with Crohn's disease within the wider sociocultural context. However, few published studies [19,24,25] have focused on the process of posttraumatic growth in these patients. Therefore, the objective of this…”
mentioning
confidence: 99%